PENGARUH SHORT-FORM VIDEO TERHADAP PERILAKU KONSUMEN: SEBUAH SYSTEMATIC LITERATURE REVIEW - Lestari, Dea Delia (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The development of social media has driven the popularity of short-form video (SFV) as one of the most influential forms of digital content in shaping consumer behavior. This study aims to identify the elements in SFV that influence consumer behavior as well as analyze how research trends in this field have developed in recent years. The method used is Systematic Literature Review (SLR) by reviewing nine scientific articles published by Scopus that are relevant to the topic. The results of the analysis showed that SFV influences consumer behavior through psychological and social factors, such as influencer personas, shared values, emotional responses, FoMO (), as well as perceptions of luxury. In addition, it was found that variables such as self-openness, religiosity, and cultural values play a role as mediators or moderators in these relationships. The study also reveals that research trends are shifting from a descriptive approach to more complex behavioral modeling, with a primary focus on the TikTok platform. The results of this study are expected to make a conceptual and practical contribution in understanding consumer dynamics in the era of short video content